Evaluation of the nondeterministic dynamic structural response of three-dimensional wind turbine steel towers. Issue 4 (August 2018) - Silva, José Guilherme Santos da; Oliveira, Breno de Almeida Santos
This investigation develops an analysis methodology aiming at the evaluation of the nondeterministic dynamic structural response of typical wind turbine supporting steel towers. The study was centered on the evaluation of the dynamic behaviour of an actual MM92 wind turbine tower of 2.1 MW Wind Class III IEC2a and mounted on an 80-m-high steel tower. The developed finite element modelling calibration was based on comparisons to experimental data related to an experimental modal analysis acquired on the wind tower structure. The wind tower dynamic structural response was investigated under gravity loads + rotor forces + nondeterministic wind dynamic loads. The present analysis has shown that the wind turbine first bending vibration mode represents the main peak of energy transfer of the dynamic structural response and this energy transfer becomes larger as the wind velocity is increased. Based on the von Mises stress distribution, it was verified that some regions of the wind tower started to yield but there is no plastic hinge formation in the wind tower sections.